Impact of post-monsoon crop residue burning on PM2.5 over northern India: optimizing emissions using a high-density in situ surface observation network - M. Kajino; M. Kajino; M. Kajino; K. Ishijima; J. Ching; J. Ching; K. Yamaji; K. Yamaji; R. Ishikawa; R. Ishikawa; T. Kajikawa; T. Kajikawa; et al. (Atmospheric Chemistry and Physics)
The impact of post-monsoon crop residue burning (CRB) on surface PM2.5 concentrations over the Punjab–Haryana–Delhi (PHD) region in northern India was investigated using a regional meteorology–chemistry model, NHM(WRF)-Chem, and a high-density in situ surface observation network comprising Compact and Useful PM2.5 Instrument with Gas Sensors (CUPI-G) stations. We optimized CRB emissions from 1 to 15 November 2022 using the model and surface PM2.5 observational data. The CUPI-G data from Punjab were found to be crucial for CRB emission optimization, as the CRB emissions in northern India in October and November are predominantly originating from Punjab, accounting for 80 % of the CRB emissions. The new emission inventory is referred to as OFEv1.0, with 12 h time resolution, in daytime (05:30–17:30 IST) and nighttime (17:30–05:30 IST). The total emissions in OFEv1.0, such as PM2.5, CO, organic carbon, and black carbon, were consistent with previous studies. OFEv1.0 substantially increased emissions relative to those calculated from satellite fire observation data (prior emissions). We showed that the prior PM2.5 emissions were underestimated by approximately 8.6 times in the period 1–15 November 2022 and sometimes obscured completely due to clouds or thick smoke/haze on 8 and 10 November 2022. Large differences in optimized daytime and nighttime emissions indicated the importance of diurnal variations. Daytime emissions were larger than nighttime emissions on some days but not on others, indicating that diurnal variation shape may have differed each day. The mean contribution of CRB to surface PM2.5 over PHD was 30 %–34 %, which increased to 50 %–56 % during plume events that transported pollutants from Punjab to Haryana and to Delhi. Due to insufficient performance of the meteorological model simulation on 8 and 9 November 2022 and the lack of measurement sites on the southern side of Punjab, emission optimization was not successful in the case of increased PM2.5 concentrations observed in Haryana on these days.